2020
DOI: 10.2147/ceor.s232779
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of the Peri-Operative Cost of Non-Traumatic Major Lower Extremity Amputation in Jordan</p>

Abstract: Purpose: Non-traumatic major lower extremity amputation (NMLEA) is a commonly performed procedure that presents a substantial cost burden. Patients who undergo NMLEA are usually considered as a high-risk group with significant comorbidities, which translates into a protracted peri-operative course and increased health-care costs. The primary aim of this study was therefore to perform a contemporary peri-operative cost analysis of NMLEA performed in our center. We are a major tertiary referral hospital that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…14 Lower limb amputation amongst persons with DM is associated with high risk for perioperative complications, prolonged length of stay in hospital, increased hospital costs and mortality. 15,16 Reported 30-day LLA-associated mortality rate ranges from 12% to 16% whilst annual mortality rate ranges from 43% to 48%. 16,17 The incidence of LLA can be mitigated through proper DM management, prompt identification and treatment of individuals at risk and patient self-management practices including foot care and examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Lower limb amputation amongst persons with DM is associated with high risk for perioperative complications, prolonged length of stay in hospital, increased hospital costs and mortality. 15,16 Reported 30-day LLA-associated mortality rate ranges from 12% to 16% whilst annual mortality rate ranges from 43% to 48%. 16,17 The incidence of LLA can be mitigated through proper DM management, prompt identification and treatment of individuals at risk and patient self-management practices including foot care and examination.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Lower limb amputation amongst persons with DM is associated with high risk for perioperative complications, prolonged length of stay in hospital, increased hospital costs and mortality. 15 , 16 Reported 30-day LLA-associated mortality rate ranges from 12% to 16% whilst annual mortality rate ranges from 43% to 48%. 16 , 17…”
Section: Introductionmentioning
confidence: 99%
“…Hospital length of stay (LOS) remains an important determinant of healthcare tariffs. A recent analysis of the perioperative cost of major LEA in Jordan identified that LOS remains the principal contributor to the final toll of major LEA [ 59 ]. In the United States, the cost of diabetic foot-related complications exceeds healthcare expenditure on the five most common cancers in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Care related to amputation, rehabilitation, and the long-term management of people with lower limb amputation is associated with significant use of health care resources. [6][7][8][9] Postoperative care that aims to maximize mobility, enables activities of daily living, and controls comorbid conditions is important to the rehabilitation process in people with lower limb amputation. 4,10 Once surgical wounds have sufficiently healed, it may be appropriate to initiate prosthesis fitting.…”
Section: Context and Policy Issuesmentioning
confidence: 99%